Biobased self-healing polyurethane coating with Zn micro-flakes for corrosion protection of AA7475 - Nardeli, Jéssica V. [UNESP] (2021)
AA7475 is a modern and competitive high strength alloy of relevance to the aerospace industry. In this work biobased organic polyurethane coatings were prepared from vegetable oils (crambe oil and castor oil) without (blank coating) and with incorporation of Zn micro-flakes to impart corrosion inhibition. Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (FTIR-ATR) confirmed the incorporation of zinc in the polymeric matrix and atomic force microscopy (AFM) confirmed the coating homogeneity. The barrier properties of the coatings were studied by electrochemical impedance spectroscopy (EIS) and indicated better corrosion resistance for the sample with the highest content of Zn micro-flakes. Localized electrochemical techniques, namely the scanning vibrating electrode technique (SVET), pH micro-potentiometry (or scanning ion-selective electrode technique - SIET) and localized electrochemical impedance spectroscopy (LEIS) permitted to discriminate the details of the corrosion inhibition process. The results demonstrated that the Zn-containing coatings provide effective corrosion protection of the AA7475 and the protective ability improved significantly in the presence of 7.5 wt% Zn micro-flakes in the coating.